Deployment of AMMI, GGE-biplot and MTSI to select elite genotypes of castor (Ricinus communis L.). Issue 2 (February 2023) - Memon, Juned; Patel, Rumit; Parmar, Dinesh J.; Kumar, Sushil; Patel, Neel A.; Patel, Bharat N.; Patel, Dipak A.; Katba, Pankaj
Abstract: Castor ( Ricinus communis L.) is an important industrial multipurpose non-edible oilseed C3 crop belongs to spurge family popularly known as Euphorbiaceae. Its oil has exceptional properties which provides an industrial importance to this crop. The present investigation is aimed to judge the stability and performance of yield and yield assigning traits and selection of suitable genotype for varied locality of western rainfed regions of India. During the study with 90 genotypes, the genotype × environment interaction was found to be significant for seed yield per plant as well as for plant height up to primary raceme, total length of primary raceme, effective length of primary raceme, capsules on main raceme and effective number of racemes per plant. E1 is the least interactive and highly representative site for seed yield. Which won where and what biplot decipher ANDCI 10-01 as vertex genotype for E3 while ANDCI 10-03 and P3 141 for E1 and E2 . Average Environment co-ordinate identify ANDCI 10-01, P3 141, P3 161, JI 357 and JI 418 as tremendously stable and high seed yielding genotypes. The study outlined the pertinency of Multi Trait Stability Index, that calculated based on the genotype-ideotype distance as the multiple interacting variables. MTSI evaluated all genotypes and sort ANDCI 12-01, JI 413, JI 434, JI 380, P3 141, ANDCI 10-03, SKI 215, ANDCI 09, SI 04, JI 437, JI 440, RG 3570, JI 417 and GAC 11 with maximum stability and high mean performance of analyzed interacting traits.